Magnetic exchange interactions in symmetric lanthanide dimetallics. Issue 20 (11th September 2020) - Giansiracusa, Marcus J.; Al-Badran, Susan; Kostopoulos, Andreas K.; Whitehead, George F. S.; McInnes, Eric J. L.; Collison, David; Winpenny, Richard E. P.; Chilton, Nicholas F.
Abstract : Multi-frequency EPR spectra and CASSCF-SO calculations on two symmetric homo-dimetallic lanthanide complexes are used to determine the magnetic exchange coupling in the low-lying states. Abstract : We report the synthesis and characterization of two symmetric homo-dimetallic lanthanide complexes based on methyl-substituted 8-hydroxyquinoline (HMeQ). The aryloxo-bridged core gives rise to weak magnetic coupling between pairs of Er III and Yb III ions, as revealed by magnetic and EPR spectroscopy studies. EPR measurements of magnetically dilute species, coupled with CASSCF-SO calculations, allows modelling of the EPR spectra of the exchange coupled species and the magnetic data simultaneously. This work adds to the database of exchange coupled {Ln}2 molecules which have been thoroughly characterised by EPR spectroscopy and modelled using an S eff = 1/2 approach to describe the interaction of ground Kramers states, and highlights the differences between centro-symmetric and asymmetric dimetallics.